5(2x-7)=3(4x+9)

Simple and best practice solution for 5(2x-7)=3(4x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-7)=3(4x+9) equation:


Simplifying
5(2x + -7) = 3(4x + 9)

Reorder the terms:
5(-7 + 2x) = 3(4x + 9)
(-7 * 5 + 2x * 5) = 3(4x + 9)
(-35 + 10x) = 3(4x + 9)

Reorder the terms:
-35 + 10x = 3(9 + 4x)
-35 + 10x = (9 * 3 + 4x * 3)
-35 + 10x = (27 + 12x)

Solving
-35 + 10x = 27 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-35 + 10x + -12x = 27 + 12x + -12x

Combine like terms: 10x + -12x = -2x
-35 + -2x = 27 + 12x + -12x

Combine like terms: 12x + -12x = 0
-35 + -2x = 27 + 0
-35 + -2x = 27

Add '35' to each side of the equation.
-35 + 35 + -2x = 27 + 35

Combine like terms: -35 + 35 = 0
0 + -2x = 27 + 35
-2x = 27 + 35

Combine like terms: 27 + 35 = 62
-2x = 62

Divide each side by '-2'.
x = -31

Simplifying
x = -31

See similar equations:

| 2x/5=x+6 | | 7m-3=3m+17 | | 4+10x=(x+9)4 | | x-5=20/5 | | 5x-1=-51 | | 9x+13=2x+174 | | t^3-5t^2+4t=0 | | -8+2x=-16 | | 12-7x=69-28x | | -4.9x^2+22t+42=0 | | 47+0.5x= | | -3-x=-1 | | 3+2x=-11 | | -5x-7=48 | | 1-4x=-11 | | 9(X-2)*2(2X-1)=8 | | 0.3x-0.5(2x+7)=-0.8(x+2) | | 6+9+x=29 | | 4x+1=11x-85 | | 5x^2-30x+225=0 | | 6+7+x=29 | | -8x-12=6x-4(3x-1) | | 2(3x-4)=8(2x+1) | | 11+7+x=35 | | 2X-X=20 | | 4+247=13-5 | | 230-6x=30x+18 | | 9-10=61-38x | | -7(-5p+4a)= | | 3x+4=52 | | 4(x+2)=2(2x+1)+6 | | f(x)=-x^3-2 |

Equations solver categories